2001
DOI: 10.1243/0954405011518926
|View full text |Cite
|
Sign up to set email alerts
|

Indicators for performance measurement in small and medium-sized enterprises

Abstract: In small and medium-sized enterprises (SMEs), resources and knowledge bases are usually strongly restricted. Therefore, it is of particular importance for these companies to be able to select and utilize only the most critical performance indicators. This could point towards a focused approach to performance measurement such as, for example, advocated in quick response manufacturing (QRM). Results from a recently conducted empirical survey of SMEs in northern Denmark are used to illustrate the present focus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 3 publications
0
44
0
2
Order By: Relevance
“…Others have already implemented BSC in small business (Fernandes, Raja, & Whalley, 2006;Andersen, 2001;Gumbus and Lussier, 2006). On the other hand, some researchers who have assessed the implementation of BSC in SMEs claim that this model is not suitable for SMEs (McAdam, 2000;Hvolby and Thorstenson, 2000). All these studies will be explained in more details to differentiate between these points of view.…”
Section: The Ability Of Smes For Implementing Bscmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have already implemented BSC in small business (Fernandes, Raja, & Whalley, 2006;Andersen, 2001;Gumbus and Lussier, 2006). On the other hand, some researchers who have assessed the implementation of BSC in SMEs claim that this model is not suitable for SMEs (McAdam, 2000;Hvolby and Thorstenson, 2000). All these studies will be explained in more details to differentiate between these points of view.…”
Section: The Ability Of Smes For Implementing Bscmentioning
confidence: 99%
“…On the other hand, Hvolby and Thorstenson (2000) claim the likelihood of significant difficulties in implementing the BSC in SMEs, as resources are typically scarce. They advocate the adoption of Quick Response Manufacturing (QRM) as an alternative to the BSC.…”
Section: The Ability Of Smes For Implementing Bscmentioning
confidence: 99%
See 1 more Smart Citation
“…They indicated that these results because these firms do not have the same pressures as large firms to meet the requirements and expectations of different stakeholder groups. In addition, Hvolby and Thorstenson (2001) indicated that financial measures are also likely to be more appealing to managers of the small and medium firms because these measures are available at a minimum cost and effort, generally relying on information which is readily provided by their financial accounting system. In addition, Perera and Baker (2007) reported that the small and medium firms have less need to develop and implement sophisticated measurement systems like balanced scorecard because managers of such firms are often able to manage the operational activities of the firms by themselves and take the necessary actions.…”
Section: Performance Measurement and Firm Sizementioning
confidence: 99%
“…SMEs do not face the same degree of pressure as large organisations to meet the requirements and expectations of different stakeholder groups. Financial measures are also likely to be more appealing to entrepreneurs and managers of SMEs because they are available at a minimum cost and effort, generally relying on information which is readily available from their financial accounting system (Hvolby and Thorstenson, 2001). In addition, SMEs have less need to develop and implement multi-dimensional measurement systems because managers of such organisations are often able to oversee operational activities of the organisation by themselves and take the necessary actions.…”
Section: Introductionmentioning
confidence: 99%